HETU: a new high‐resolution stress and texture neutron diffractometer at China Mianyang Research Reactor - Wang, Baihua; Zhong, Shengyi; Lin, Hao; Goukassov, Arsen; Yang, Zhaolong; Li, Jian; Sun, Guang-ai (Journal of applied crystallography, 2023)
HETU is a new high‐resolution stress and texture neutron diffractometer installed at the C1 neutron guide at China Mianyang Research Reactor. The diffractometer is designed for precise residual stress and texture analysis of engineering components, as well as in situ investigations under various sample environments for engineering materials. The wavelength range of monochromatic incident neutrons is 1.634–5.800 Å, provided either by a double‐focusing perfect single‐crystal silicon monochromator in high instrument resolution mode or by a highly oriented pyrolytic graphite monochromator in high neutron flux mode. The intrinsic peak widths of HETU have been measured using a standard silicon powder sample, and residual stress measurements of an aluminium alloy shrink‐fit ring and plug have been carried out. These results demonstrate that HETU is a reliable and appropriately designed diffractometer for promoting materials investigation. A new high‐resolution stress and texture neutron diffractometer that utilizes long‐wavelength neutrons to evaluate residual stress and analysis texture is presented.